DỰ BÁO THỜI HẠN BẢO QUẢN THUỐC PHÓNG PYROCXILIN TRONG ĐIỀU KIỆN BAO GÓI KÍN BẰNG PHƯƠNG PHÁP THỬ NGHIỆM GIA TỐC - Hà, Hữu Sơn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ACCELERATED METHOD TO ESTABLISH THE WARRANTY STORAGE TIME OF PYROXYLIN PROPELLANTS IN TROPICAL CLIMATE CONDITIONSStandard OCT B 84-2433-90 (Russia) prescribed acceleration method to predict preservation time and using time of pyroxylin propellants. This paper introduces the result of application of the standard to some pyroxylin mark 7/14 in Vietnam conditions based on the decline content of Diphenylamine (DPA). The preservation time was calculated quite reliably.